Caracterización del aceite esencial de Hyptis capitata Jacq mediante pruebas fisicoquímicas y cromatografía de gases acoplada a espectrometría de masas - Panaifo Cárdenas, Lloni (2024)
Hyptis capitata is a plant of the Lamiaceae family used in folk medicine to fight infections caused by fungi and against harmful insects, the flower in our study has a sui-generis odor. The study aimed to extract the essential oil, characterize it by measuring its physicochemical properties, and determine the chemical components by chromatographic analysis. The sample was collected in the hamlet of Uchpagallo on the banks of the Amazon River, district of Belen, Maynas, Loreto. The oil was obtained by hydrodistillation, the physicochemical parameters were estimated and the components were identified by GC-MS analysis. A yield of 0.164 %, density 0.8646 g/mol, refractive index 1.462 was obtained. The chromatogram showed the presence of 43 components, the most abundant were β-linalool 30.95 %, α-Pinene 14.13 %, Nonane 10.62 %, β-Caryophyllene 7.49 % and α-Caopaene 5.62 %. The nature of the secondary metabolites present in the essential oil suggests that they should be used in the perfume, cosmetics, and pharmaceutical industries.